Psychopathy and Antisocial Personality: A Critical Review of Concepts, Assessment, and the Risk of Mislabeling in Forensic Clinical Practice - Khalil Gibran Kadir (Punggawa Legacy Center, 2026)
The use of psychopathy in clinical–forensic contexts has remained conceptually contentious and operationally consequential, particularly when it has been treated as interchangeable with antisocial personality disorder. This article examined how construct confusion and assessment practices contributed to mislabeling and to downstream legal and clinical decisions. A qualitative, library-based secondary-data approach was used through a critical narrative review of peer-reviewed journal literature published within the last five years. The synthesis organized findings into three themes: conceptual boundaries between psychopathy and antisocial personality disorder, measurement and inference constraints in psychopathy assessment, and mechanisms through which mislabeling occurred in applied settings. The review found that psychopathy functioned as a multidimensional trait construct requiring evidence of interpersonal and affective features, whereas antisocial personality disorder operated as a behavior-anchored diagnosis, and collapsing these categories promoted score-driven inference, base-rate neglect, and confounding with trauma, substance use, and other clinical conditions. The article proposed operational safeguards emphasizing multi-source evidence, facet-level interpretation, and probabilistic reporting to reduce mislabeling while maintaining risk-responsive practice.